2020
DOI: 10.1590/1516-4446-2018-0333
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in activities of daily living are associated with stigma in patients with Parkinson’s disease who are candidates for deep brain stimulation

Abstract: Objective: Parkinson's disease (PD) is often accompanied by stigma, which could contribute to a worse prognosis. The objective of this study is to identify the variables associated with stigma in PD patients who are candidates for deep brain stimulation (DBS). Methods: We investigated sociodemographic and clinical variables associated with stigma in a sample of 54 PD patients indicated for DBS. The independent variables were motor symptoms assessed by the Movement Disorder Society-sponsored revision of the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results were also inconsistent: depression has been reported to correlate with self-stigma in four studies (Schrag et al, 2001;Oguru et al, 2010;Ma et al, 2016;Salazar et al, 2019) but not in another three studies (Chapuis et al, 2005;Wu et al, 2014;da Silva et al, 2020). Younger age has been reported to correlate with self-stigma in two studies (Wu et al, 2014;Salazar et al, 2019) but not in another five studies (Schrag et al, 2001;Chapuis et al, 2005;Oguru et al, 2010;Ma et al, 2016;da Silva et al, 2020), while apathy, difficulties in ADL, non-motor symptoms, H&Y stage, marital status, biphasic dyskinesia, morning akinesia, end-ofdose fluctuations, and unpredictable offs have been reported to correlate with self-stigma only in a single study (Chapuis et al, 2005;Oguru et al, 2010;Wu et al, 2014;da Silva et al, 2020). The heterogeneous results might partially ascribe to the different cultural backgrounds as self-stigma originates in the social context (Major and O'Brien, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results were also inconsistent: depression has been reported to correlate with self-stigma in four studies (Schrag et al, 2001;Oguru et al, 2010;Ma et al, 2016;Salazar et al, 2019) but not in another three studies (Chapuis et al, 2005;Wu et al, 2014;da Silva et al, 2020). Younger age has been reported to correlate with self-stigma in two studies (Wu et al, 2014;Salazar et al, 2019) but not in another five studies (Schrag et al, 2001;Chapuis et al, 2005;Oguru et al, 2010;Ma et al, 2016;da Silva et al, 2020), while apathy, difficulties in ADL, non-motor symptoms, H&Y stage, marital status, biphasic dyskinesia, morning akinesia, end-ofdose fluctuations, and unpredictable offs have been reported to correlate with self-stigma only in a single study (Chapuis et al, 2005;Oguru et al, 2010;Wu et al, 2014;da Silva et al, 2020). The heterogeneous results might partially ascribe to the different cultural backgrounds as self-stigma originates in the social context (Major and O'Brien, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Self-stigma in neuropsychiatric diseases may lead to harmful consequences, such as social isolation, delayed search for medical help, non-adherence to treatment, and increased suicide rates (Corrigan, 2004;Schomerus et al, 2015). Previous studies have shown that self-stigma is a key determinant of health-related quality of life in PD (Ma et al, 2016), and it is associated with difficulties in activities of daily living (ADL) (da Silva et al, 2020) and high burden for caregivers (Tan et al, 2019) in patients with PD. Thus, studying the determinants of self-stigma in PD might help to intervene and reduce it.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of unemployment from EOPD goes beyond a financial cost, including social isolation, feelings of futility, lack of purpose and self‐esteem, and lack of daily structure. Many patients with PD are most bothered by the perception that others might have of their impairment than by their impairment itself 141,142 . This higher level of stigma in patients with EOPD 17,143 seems to stem essentially from dysarthria, tremor, dyskinesia, and impact of the motor symptoms on activities of daily living such as eating and washing 144 and can manifest as a reluctance to seek help and ask for adjustments at work, which in turn decreases the chances of staying employed.…”
Section: Impact Of Pd On Employment and Social Perceptionmentioning
confidence: 99%
“…Meanwhile, invisible stigma is the realization of a self with PD, a form of disability, which attested to the mounting isolation (11). Recently, a few studies revealed that difficulties in activities of daily living, younger age, and higher depression scores were the significant predictors of stigma (13,14). However, relative studies are limited in China.…”
Section: Introductionmentioning
confidence: 99%